Dampak Empowering Leadership, Psychological Empowerment, Job Satisfaction Dan Emotional Intelligence Terhadap Organizational Commitment Tenaga Kesehatan Generasi Z Di Rumah Sakit - Diah Kurnia Yussela; Rojuaniah Rojuaniah (Lembaga Komunitas Informasi Teknologi Aceh (KITA), Indonesia, 2026)
The low level of organizational commitment among Generation Z healthcare workers has become a serious challenge for hospitals in maintaining service sustainability and quality. This study aims to analyze the effect of empowering leadership on psychological empowerment, job satisfaction, and emotional intelligence, as well as their impact on the organizational commitment of Generation Z healthcare workers in hospitals. This study adopts a quantitative approach using a survey method. The population consists of Generation Z healthcare workers employed in hospitals, with a sample of 165 respondents working in hospitals in the Jakarta region. Data were analyzed using Structural Equation Modeling-Partial Least Squares (SEM-PLS). The results indicate that empowering leadership has a positive effect on psychological empowerment, job satisfaction, and emotional intelligence. Furthermore, psychological empowerment, job satisfaction, and emotional intelligence are proven to have a positive effect on organizational commitment. These findings highlight that empowering leadership plays a strategic role in fostering positive psychological conditions and enhancing organizational commitment among Generation Z healthcare workers. Practically, this study provides managerial implications for hospitals in developing adaptive leadership styles, strengthening psychological empowerment, and managing emotional well-being to improve loyalty and organizational commitment among Generation Z healthcare workers.